2020
DOI: 10.3389/fmicb.2020.02065
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity Factors of Genomic Islands in Intestinal and Extraintestinal Escherichia coli

Abstract: Escherichia coli is a versatile bacterial species that includes both harmless commensal strains and pathogenic strains found in the gastrointestinal tract in humans and warmblooded animals. The growing amount of DNA sequence information generated in the era of "genomics" has helped to increase our understanding of the factors and mechanisms involved in the diversification of this bacterial species. The pathogenic side of E. coli that is afforded through horizontal transfers of genes encoding virulence factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
106
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(109 citation statements)
references
References 483 publications
(690 reference statements)
3
106
0
Order By: Relevance
“…A panel of 8 diverse AIEC clinical strains isolated from 8 different CD patients was used to evaluate the clinical relevance of OmpR as a drug target ( Table 1 ). All the strains belonged to distinct sequence types and encoded different FimH variants, reflecting the genotypic variability of the AIEC group ( Desvaux et al, 2020 ). Except for the strain S179, all AIEC strains belonged to the S70/N78 FimH clade, conferring higher ability to adhere to intestinal epithelial cells ( Dreux et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…A panel of 8 diverse AIEC clinical strains isolated from 8 different CD patients was used to evaluate the clinical relevance of OmpR as a drug target ( Table 1 ). All the strains belonged to distinct sequence types and encoded different FimH variants, reflecting the genotypic variability of the AIEC group ( Desvaux et al, 2020 ). Except for the strain S179, all AIEC strains belonged to the S70/N78 FimH clade, conferring higher ability to adhere to intestinal epithelial cells ( Dreux et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…This is in agreement with previous studies [24,60] which reported PAI IV536 as the most prevalent PAI. The main virulence genes residing in the PAI IV536 and PAI IICFT073 are yersiniabactin siderophore iron-uptake system and P. mbriae as well as iron regulated proteins respectively [61,63,64]. A previous study in Uganda reported high prevalence of E. coli with P. mbriae virulent factor encoded for by the pap gene in UPEC [65]indicating high prevalence of PAI IICFT073 pathotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, existence of virulence genes and genetic determinants of resistance in phylogenetic groups A and D where commensal mainly fall should be treated as a major threat as they are considered to reservoirs of genetic determinants of virulence and antibiotic resistance and they donate these traits to the pathogenic strains of phylogroups B1 and B2 through horizontal gene transfer, arbitrated regularly by plasmids and transposons [44]. Indeed, previous studies observed that PAIs are mobile genetic elements (transposons) that are transferred from one E. coli strain to another through horizontal gene transfer mediated by bacteriophages, conjugative plasmids, conjugation and homologous DNA recombination [64,81,82]…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with previous studies [22,65] which reported PAI IV536 as the most prevalent PAI. The main virulence genes residing in the PAI IV536 and PAI IICFT073 are yersiniabactin siderophore iron-uptake system and P. fimbriae as well as iron regulated proteins respectively [66,68,69]. A previous study in Uganda reported high prevalence of E. coli with P. fimbriae virulent factor encoded for by the pap gene in UPEC [70]indicating high prevalence of PAI IICFT073 pathotypes.…”
Section: Extraintestinal Pathogenic Escherichia Coli (Expec)mentioning
confidence: 99%
“…Furthermore, existence of virulence genes and genetic determinants of resistance in phylogenetic groups A and D where commensal mainly fall should be treated as a major threat as they are considered to reservoirs of genetic determinants of virulence and antibiotic resistance and they donate these traits to the pathogenic strains of phylogroups B1 and B2 through horizontal gene transfer, arbitrated regularly by plasmids and transposons [49]. Indeed, previous studies observed that PAIs are mobile genetic elements (transposons) that are transferred from one E. coli strain to another through horizontal gene transfer mediated by bacteriophages, conjugative plasmids, conjugation and homologous DNA recombination [69,85,86].…”
Section: Extraintestinal Pathogenic Escherichia Coli (Expec)mentioning
confidence: 99%